2022
DOI: 10.3390/cancers14194962
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Occupational Exposure to Heavy Metals and Welding Fumes and Testicular Germ Cell Tumours in Sons in France

Abstract: Testicular cancer is the most common cancer in young men. Its causes are largely unknown, although prenatal occupational and environmental exposures have been suggested. We investigated paternal occupational exposure to heavy metals and welding fumes and the risk of testicular germ cell tumors (TGCT) in their offspring. A total of 454 cases and 670 controls were included from a French nationwide case–control study. The INTEROCC job exposure matrix was used to assign occupational exposures (cadmium, chromium, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…It should be noted that the few associations identified in this study presented plausible hypotheses consistent with the results of previous experimental and human studies (18,21,22). Finally, because of the study design, we had to assume that the parental job at birth reflected the exposure at the time of conception and during intrauterine development, following the example of other studies (21,22,37) even though a change in employment may have occurred during these periods. In the TESTIS study, upon written consent by the participants, the participants' mothers were also contacted to offer them participation in the study and a telephone interview.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…It should be noted that the few associations identified in this study presented plausible hypotheses consistent with the results of previous experimental and human studies (18,21,22). Finally, because of the study design, we had to assume that the parental job at birth reflected the exposure at the time of conception and during intrauterine development, following the example of other studies (21,22,37) even though a change in employment may have occurred during these periods. In the TESTIS study, upon written consent by the participants, the participants' mothers were also contacted to offer them participation in the study and a telephone interview.…”
Section: Discussionsupporting
confidence: 67%
“…This study documents the relationship between parental occupational exposure to solvents and TGCT risk among their offspring in France. Parental occupation at birth was considered as a proxy of solvent exposure before and at conception (37). No solid evidence of an association between parental occupational exposure to solvents at birth and TGCT among sons was found.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies on the different occupational exposures related to these jobs and industries of the parents at birth are needed, as we have done or plan to do with solvents, pesticides, or heavy metals ( 87 ). In addition, the combined effect of early life exposure, leading to the development of GCNIS, and later life exposure in adolescence or adulthood, acting as a trigger for the evolution of GCNIS to TGCT, should be taken into account in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Testicular germ cell tumors (TGCTs) are the most common cancers in young adult men 1 . The reason is unknown, although it has been suggested that it may be related to prenatal occupational and environmental exposures 2 . There are significant regional differences in the incidence of testicular cancer, especially in young men in Europe 3 .…”
Section: Introductionmentioning
confidence: 99%